The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/wdev.90
|View full text |Cite
|
Sign up to set email alerts
|

Neural induction and early patterning in vertebrates

Abstract: In vertebrates, the development of the nervous system is triggered by signals from a powerful 'organizing' region of the early embryo during gastrulation. This phenomenon--neural induction--was originally discovered and given conceptual definition by experimental embryologists working with amphibian embryos. Work on the molecular circuitry underlying neural induction, also in the same model system, demonstrated that elimination of ongoing transforming growth factor-β (TGFβ) signaling in the ectoderm is the hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 153 publications
2
68
0
Order By: Relevance
“…For example, loss of the miRNA pathway might reveal a default neural program, which was reported as the ground differentiation state of the vertebrate ectoderm (Chang and Hemmati-Brivanlou, 1998;Ozair et al, 2013). Curiously, Mei-P26 is another factor with specific (although not exclusive) neural expression that is derepressed in non-neuronal miRNA pathway mutant clones (Herranz et al, 2010).…”
Section: Gw182-rnaimentioning
confidence: 99%
“…For example, loss of the miRNA pathway might reveal a default neural program, which was reported as the ground differentiation state of the vertebrate ectoderm (Chang and Hemmati-Brivanlou, 1998;Ozair et al, 2013). Curiously, Mei-P26 is another factor with specific (although not exclusive) neural expression that is derepressed in non-neuronal miRNA pathway mutant clones (Herranz et al, 2010).…”
Section: Gw182-rnaimentioning
confidence: 99%
“…The grafted cells contributed to axial mesodermal derivatives (such as the notochord), whereas the nervous system (with the exception of the floor plate) was derived from the host. Importantly, this experiment established that symmetry breaking is caused by localized inductive signals (Ozair et al, 2013;Spemann and Mangold, 1924). In asking how early these symmetry-breaking signals are established, it was shown that two to three blastomeres of an eight-cell stage Xenopus embryo are sufficient to give rise to a second body axis when transplanted into a 64-cell embryo (Gimlich and Gerhart, 1984).…”
Section: Breaking Symmetrymentioning
confidence: 95%
“…T he central nervous system originates from a small number of cells proliferating during early development from the neural plate [1], which reaches a number of hundreds of billions neurons in higher mammals [2]. This process named neurogenesis involves cell division, migration, differentiation, and interaction of cells to form an extremely dynamic, functional network.…”
Section: Introductionmentioning
confidence: 99%